PENELITIAN KEAGAMAAN INTEGRATIF-INTERKONEKTIF Implementasi Pendekatan Integrasi dan Interkoneksi Keilmuan dalam Skripsi-skkripsi Jurusan PA (1994-2004) - ahmad muttaqin (Religi: Jurnal Studi Agama-agama, 2018)
This paper analyses the implementation of integration and interconnection approaches among undergraduate thesis in the department of Comparative Religion (now Religious Studies) at the Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia. It shows that 62% of the undergraduate theses have implemented semipermeable model, 38% intersubjective testability, and none of them have implemented creative imagination. The absent of creative imagination model is understandable because referring to the Indonesian Qualification Framework Curriculum (KKNI) that the competency of S1-student is on the standard 6th: which is capable for doing analyses. The creative imagination model seems to fit more for student at doctoral level (standard 9th), in which they are required to find new theories in their doctoral thesis.